2004
DOI: 10.1016/j.ijgo.2004.09.017
|View full text |Cite
|
Sign up to set email alerts
|

l‐Arginine treatment for asymmetric fetal growth restriction

Abstract: A deficiency in nitric oxide may play an important role in the development of asymmetric fetal growth restriction. L-Arginine can be used to increase maternal NO2-/NO3- levels and newborn birth weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
1
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 7 publications
2
58
1
2
Order By: Relevance
“…Gene expression and protein tissue content of arginase II (enzyme that degrades arginine to ornithine) were found to be higher in preeclamptic villi than in normotensive pregnancy [12]. Arginase II over-expression is seen in lower L-arginine concentration which causes increase in peroxynitrite (isoform of nitric oxide synthase).…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression and protein tissue content of arginase II (enzyme that degrades arginine to ornithine) were found to be higher in preeclamptic villi than in normotensive pregnancy [12]. Arginase II over-expression is seen in lower L-arginine concentration which causes increase in peroxynitrite (isoform of nitric oxide synthase).…”
Section: Discussionmentioning
confidence: 99%
“…35,36 Maternal nitrite/nitrate plasma levels have been found to be decreased in pregnancies with intrauterine growth restriction. 37,38 Treatment with the NO donor L-arginine was able to increase birth weight in those cases. 38,39 A small study reported that fetuses of women with at least one rare allele of the NOS3 VNTR 4a/b polymorphism weigh less at birth.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 Treatment with the NO donor L-arginine was able to increase birth weight in those cases. 38,39 A small study reported that fetuses of women with at least one rare allele of the NOS3 VNTR 4a/b polymorphism weigh less at birth. 40 According to the results from our large study population, the analysed maternal NOS3 polymorphisms do not influence fetal growth and birth weight.…”
Section: Discussionmentioning
confidence: 99%
“…For example, during late (week 33) gestation, daily intravenous infusion of arginine (20 g/day) for 7 days to women with unknown causes of IUGR increased birth weight at term (week 39) by 6.4% (Xiao and Li, 2005). Moreover, results of a more recent study indicated that administration of Arg to women with an IUGR fetus was effective in reducing placental apoptosis and improving fetal growth and development (Shen and Hua, 2011).…”
Section: Argininementioning
confidence: 99%